Analisis Ramuan Obat Tradisional untuk Wasir di Pulau Jawa; Studi Etnofarmakologi RISTOJA 2015 - Peristiwan R Widhi Astana; Ulfatun Nisa (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
The using of traditional medicine among community has being accepted and become huge potency to be developed by our country. One of disease which is often treated with traditional medicine is hemorrhoid or in bahasa as known as “wasir”. According to the result of ethopharmacology research of traditional medicine and jamu (RISTOJA) 2015 in java island, there are several formulas used by traditional healers to treat hemorrhoid. In order to fi nd potential formulas to be developed, a descriptive study was conducted involving identifi cation of medicinal plant and also literature study about its benefi t and toxicity evidences. The plants which named in formula’s ingredient were analized to see how important and utility value for hemorrhoid treatment. Literature study was conducted to assess potential benefi t and toxicity. The result said there were 37 species of medicinal plant in 25 family used in traditional medicine formula for hemorrhoid. Based on Frequency Citation(FC), Utility Value (UC) and literature study, Graptophyllum pictum (L.) Griff ., Curcuma longa L., Aloe vera (L.) Burm.F, and Musa balbisiana have enough scientifi c evidence to be studied further development.